STATUS GIZI AWAL KEHAMILAN DAN PERTAMBAHAN BERAT BADAN IBU HAMIL KAITANNYA DENGAN BBLR - Yongky Yongky; Hardinsyah Hardinsyah; Gulardi Gulardi; Marhamah Marhamah (Jurnal Gizi dan Pangan, 2009)
The objectives of this research were to analyze nutritional status of pregnant women in Jakarta Timur and Bekasi and the accretion of body weight and its relationship with low birth weight. As many as 638 pregnant women had been followed since first examination until delivery. At the first trimester, most of pregnant women (53.8%) were categorized as normal nutritional status (BMI 19.8-26); underweight (BMI <19.8) 40%; and overweight (BMI > 26.01) 6.2%. The accretion of pregnant women body weight was relatively higher in high socio-economic status rather than low socio-economic status. The prevalence of low birth weight was higher among mothers from low socio-economic status. It is important for pregnant women to pay attention on her nutritional status in the early pregnancy and the accretion of body weight.